2021
DOI: 10.3389/fmed.2021.679171
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Extracellular Vesicles for Renal Tubular Transporters Expression in Patients With Gitelman Syndrome

Abstract: Background: The utility of urinary extracellular vesicles (uEVs) to faithfully represent the changes of renal tubular protein expression remains unclear. We aimed to evaluate renal tubular sodium (Na+) or potassium (K+) associated transporters expression from uEVs and kidney tissues in patients with Gitelman syndrome (GS) caused by inactivating mutations in SLC12A3.Methods: uEVs were isolated by ultracentrifugation from 10 genetically-confirmed GS patients. Membrane transporters including Na+-hydrogen exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…To isolate uEVs, the collected urine was centrifuged at 17 000× g and 37°C for 10 min, and the supernatant was ultracentrifuged at 200 000× g for 2 h at 4°C. The pellet was resuspended in Laemmli buffer with dithiothreitol for immunoblotting (IB) 37,38 …”
Section: Methodsmentioning
confidence: 99%
“…To isolate uEVs, the collected urine was centrifuged at 17 000× g and 37°C for 10 min, and the supernatant was ultracentrifuged at 200 000× g for 2 h at 4°C. The pellet was resuspended in Laemmli buffer with dithiothreitol for immunoblotting (IB) 37,38 …”
Section: Methodsmentioning
confidence: 99%
“…In patients with Gitelman syndrome, uEV analysis also reflects the changes that occur in unaffected nephron segments to compensate for salt wasting. Although NCC was absent or reduced, NHE3, β-ENaC, and pendrin were increased both in uEVs and in kidney biopsies of patients with Gitelman syndrome [37]. Conversely, uEV abundances of NCC and pNCC were increased in patients with familial hyperkalemic hypertension, a mirror image of Gitelman syndrome caused by genetic variants in NCC regulating kinases or ligases, including WNK1, WNK4, KLHL3, or cullin-3 [3,38].…”
Section: Inherited Tubulopathiesmentioning
confidence: 96%
“…In addition, Raimondo et al investigated the proteome of uEVs and set up a panel of 5 proteins, including carbonic anhydrase (CA2), vacuolar-type ATPase B subunit 1 (VATB1), Annexin A2 (ANXA2), sodium chloride cotransporter (NCC), and NKCC2, which can differentiate Gitelman and Bartter syndromes (salt-losing tubulopathies) [ 116 ]. Sung et al also found that NCC and phosphorylated-NCC were decreased in uEVs from patients with Gitelman syndrome, while Na + -hydrogen exchanger 3 (NHE3), epithelial Na + channel β (ENaCβ), and pendrin were increased [ 117 ]. By investigating urinary microvesicles, Rood et al found the increase of lysosome membrane protein 2 (LIMP-2) from patients with idiopathic membranous nephropathy, and the upregulation of LIMP-2 was identified in renal biopsies that the protein was co-localized with IgG along the glomerular basement membrane [ 118 ].…”
Section: Proteomics-based Studies Of Exosomes/sevs For Kidney Diseasesmentioning
confidence: 99%